Terrorismes en mutation : Déshumanisation et espoirs - El Khoury, Emilie (Anthropologica, 2025)
Twenty-three years after the September 11, 2001 attacks, anthropological analysis remains crucial to understanding the complex dynamics of terrorism and violence. Anthropology, as a discipline dedicated to studying humanity, allows us to understand that violence is not an isolated phenomenon, but an oft- instrumentalized tool to control societies and shape power relations. Although the events of September 11 are frequently associated with religious extremism, it is important to highlight that terrorism is a multi-faceted phenomenon, fuelled by a variety of ideological, cultural and social factors. One striking characteristic of contemporary terrorism is the dehumanization of victims, often reduced to abstractions, such as “human losses” or “number of dead.” Concurrently, those responsible for the violence are sometimes portrayed as “monsters,” a reciprocal mechanism of dehumanization. This process prevents the true recognition of individual suffering, while hindering a deeper reflection on the social, political and economic reasons for violence. Anthropology provides valuable insight into these mechanisms and paves the way to more effectively preventing future violence. The current interconnected generation plays a key role in transforming these perceptions by rejecting—or not—violent responses in favour of solutions that are more inclusive, supportive, and adapted to local realities.